1996
DOI: 10.1097/00003246-199610000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for the prevention of postextubation airway obstruction

Abstract: Pretreatment with dexamethasone decreases the frequency of postextubation airway obstruction in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The frequency of pediatric reintubation for stridor ranges from 2% to 52% 72-77 . Other variables related to stridor included the number of racemic epinephrine treatments 73,76-80 , use of a helium-oxygen gas mixture 73 , and stridor requiring some form of intervention 74,77 . Two RCTs evaluating the use of dexamethasone to prevent post-extubation stridor reported reintubation in 11% 73 and 25% 74 of patients with stridor.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of pediatric reintubation for stridor ranges from 2% to 52% 72-77 . Other variables related to stridor included the number of racemic epinephrine treatments 73,76-80 , use of a helium-oxygen gas mixture 73 , and stridor requiring some form of intervention 74,77 . Two RCTs evaluating the use of dexamethasone to prevent post-extubation stridor reported reintubation in 11% 73 and 25% 74 of patients with stridor.…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistency in the assessment of a clinical outcome such as post extubation UAO may in part explain why few therapeutic studies on post-extubation stridor have demonstrated a benefit 2,5,13,14 . Directly meaningful outcomes for therapeutic studies, such as re-intubation secondary to UAO, are relatively rare when applied to the global PICU population (4 or 5 of the 112 extubations in our study would have met these criteria (3.6–4.5%)).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rates for post-extubation UAO range from 6–69 %, and result in reintubation 2–22% of the time 25 . Based on clinical grounds alone, it is estimated that up to 1/3 of all failed extubations result from UAO 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, determination of arterial blood gases. All the children were then deeply sedated with a continuous infusion physicians of the mobile critical care units of the for the risk of mortality were found previously in a ISS similar population of injured children and Median (SD) 28 (25)(26)(27)(28)(29)(30)(31)(32)(33) determined as a PTS < 4, a GCS < 7 and an ISS > 25.…”
Section: Methodsmentioning
confidence: 99%